2006
DOI: 10.1097/01.id.0000245440.09464.48
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Analysis of Implant Screw Torque Loss With External Hex and Internal Connection Implant Systems

Abstract: It may be concluded from this study that although internal connections are clinically favored, this study did not show any advantage relative to screw loosening. However, screw design may be a significant factor in loosening of the joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
39

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 11 publications
4
78
1
39
Order By: Relevance
“…The load was applied with a metal cylinder with 4 mm in diameter. The machine was set to work at a frequency of 101 cycles per minute, simulating to the human chewing frequency 26 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…The load was applied with a metal cylinder with 4 mm in diameter. The machine was set to work at a frequency of 101 cycles per minute, simulating to the human chewing frequency 26 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…This indicated that there was mechanical resistance in the lower lobe. Piermatti et al 25 studied the shape of the implant abutment screw and the stability of the connection; they reported that the torque decreased when a thicker, special form of screw was used. In this study, we used screws with a thread of 2.0 mm and a long upper part with a thickness of 2.5 mm; this could have stabilized the connection between the implant abutment and the fixture, and thus, prevented differences in the removal torques.…”
Section: Discussionmentioning
confidence: 99%
“…The implant-abutment connection stability is also influenced by factors such as component fit, machining accuracy, saliva contamination, and screw preload. [1][2][3][4][5][6][7][8] Most in vitro studies, [9][10][11][12] with the exception of one, 13 have demonstrated that internal connections are more mechanically stable than external flat (hex-type) connections. Loosening of abutment screws, particularly with the "classic" external-hex implant systems, has been a well-known technical problem, occurring mainly during the first 2 years after delivery of the crown.…”
mentioning
confidence: 99%